Male sterility and reduced female fertility in SCAPER-deficient mice. (8th June 2020) - Tatour, Yasmin; Bar-Joseph, Hadas; Shalgi, Ruth; Ben-Yosef, Tamar
Abstract: Mutations in S-phase cyclin A-associated protein in the endoplasmic reticulum (SCAPER) cause a recessively inherited multisystemic disorder whose main features are retinal degeneration and intellectual disability. SCAPER, originally identified as a cell cycle regulator, was also suggested to be a ciliary protein. Because Scaper mutant males are sterile, we set up to characterize their phenotype. The testes of Scaper mutant mice are significantly smaller than those of WT mice. Histology revealed no signs of spermatogenesis, and seminiferous tubules contained mainly Sertoli cells with a few spermatogonia/spermatogonial stem cells (SSCs). In WT testes, SCAPER is expressed by SSCs and in the various stages of spermatogenesis, as well as in Sertoli cells. In WT spermatozoa SCAPER is not expressed in the flagellum but rather in the head compartment, where it is found both in the nucleus and in the perinuclear region. Scaper mutant females present reduced fertility, manifested by a significantly smaller litter size compared to WT females. Mutant ovaries are similar in size but comprised of significantly less primordial and antral follicles, compared to WT ovaries, while the number of atretic follicles is significantly higher. In WT ovarian follicles SCAPER is expressed in the somatic granulosa cells as well as in the oocyte. In conclusion, our data demonstrate that SCAPER is a crucial component in both male and female reproductive systems. We hypothesize that the reproductive phenotype observed in Scaper mutant mice is rooted in SCAPER's interaction with cyclin A/Cdk2, which play an important role, however different, in male and female gonads.